2018
DOI: 10.1016/j.jmps.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Increasing damage tolerance in composites using hierarchical brick-and-mortar microstructures

Abstract: Composites are attractive materials because of their high specific stiffness and specific strength, but their application in industry is restricted by their inherent lack of damage tolerance and stable energy dissipation mechanisms, due to the brittleness of the fibres. Nature overcomes a similar issue by arranging natural composites, made of mostly brittle constituents, in discontinuous and hierarchical microstructures. This work aims at evaluating the potential of hierarchical discontinuous carbon-fibre rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…The multiple hierarchical levels found in many biological composites further improve their mechanical responses and failure properties Wei et al, 2015;Gao et al, 2016;Henry and Pimenta, 2018). It has been shown that hierarchal microstructures provide improved resiliency to stress concentrations near inclusions (Gorbatikh et al, 2010) and enhanced damage dispersion (Ritchie, 2011;Dutta and Tekalur, 2014;Mirzaeifar et al, 2015;Henry and Pimenta, 2018). These observations are part of a large and ever growing body of work establishing that staggered microstructures tend to be the most favorable architectures for simultaneously producing stiffness, strength, and toughness in thin, macroscopic materials (Espinosa et al, 2009;Zhang Z. Q. et al, 2010;Barthelat and Zhu, 2011;Dutta et al, 2013;Barthelat, 2014;Ni et al, 2015;Pro et al, 2015;Qwamizadeh et al, 2015Qwamizadeh et al, , 2017aAbid et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…The multiple hierarchical levels found in many biological composites further improve their mechanical responses and failure properties Wei et al, 2015;Gao et al, 2016;Henry and Pimenta, 2018). It has been shown that hierarchal microstructures provide improved resiliency to stress concentrations near inclusions (Gorbatikh et al, 2010) and enhanced damage dispersion (Ritchie, 2011;Dutta and Tekalur, 2014;Mirzaeifar et al, 2015;Henry and Pimenta, 2018). These observations are part of a large and ever growing body of work establishing that staggered microstructures tend to be the most favorable architectures for simultaneously producing stiffness, strength, and toughness in thin, macroscopic materials (Espinosa et al, 2009;Zhang Z. Q. et al, 2010;Barthelat and Zhu, 2011;Dutta et al, 2013;Barthelat, 2014;Ni et al, 2015;Pro et al, 2015;Qwamizadeh et al, 2015Qwamizadeh et al, , 2017aAbid et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…While significantly contributing to small strain behaviors, these interfaces also provide robust toughening mechanisms through stable energy dissipation (Mayer, 2005;Barthelat et al, 2012). The multiple hierarchical levels found in many biological composites further improve their mechanical responses and failure properties Wei et al, 2015;Gao et al, 2016;Henry and Pimenta, 2018). It has been shown that hierarchal microstructures provide improved resiliency to stress concentrations near inclusions (Gorbatikh et al, 2010) and enhanced damage dispersion (Ritchie, 2011;Dutta and Tekalur, 2014;Mirzaeifar et al, 2015;Henry and Pimenta, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…with different objectives. For instance, developing architectured porous materials for structural, acoustic and insulation properties [40,70], entangled monofilament of pearlitic steel [47,173], sandwich composite structures [118,[163][164][165], segmented interlocking structures [59,60,62,65,66,72,117,123,136,[145][146][147]189], asymmetric frictional materials [18,19], woven and non-woven textile composites [57,130,141], porous metallic glasses [187], hierarchical composites [92], crumpled metallic foils [34]. Much more examples can be found in the present book.…”
Section: Introductionmentioning
confidence: 99%